Plastic pipe systems : failure investigation and diagnosis - Farshad, Mahdi (Elsevier, 2006)
Industrial and domestic piping is increasingly made from various plastics and composites, and these materials withstand heavy use over long periods. They are, however, affected by environmental and other factors over time and can degrade, causing major problems within piping systems. Farshad's book deals with why plastic pipes and systems fail, and with how to investigate and diagnose such failures. Pipes may buckle, fracture, change in dimensions and colour, blister and delaminate, corrode through stress, be abraded and obstructed: all these cause problems and lead to loss of efficient operation of a system. The author's experience is backed up by a large data-base of results * Wide target audience * The only book covering the whole subject * Unique approach based on long experience.